2018
DOI: 10.18502/kss.v3i10.3397
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Marketing Mix on Loyalty Through Customer Satisfaction in PT. Merck Tbk Cabang Medan

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Khuzaini concluded that product and price are the most important variables affecting loyalty [11]. The direct effect of the product on customer loyalty is greater than the effect of the product on customer loyalty through customer satisfaction [12]. It is necessary to improve the quality of the product by increasing the composition of the product, and the promotion price should be applied in the pricing strategy [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khuzaini concluded that product and price are the most important variables affecting loyalty [11]. The direct effect of the product on customer loyalty is greater than the effect of the product on customer loyalty through customer satisfaction [12]. It is necessary to improve the quality of the product by increasing the composition of the product, and the promotion price should be applied in the pricing strategy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Using different promotions, there could be a huge opportunity for Hermes, if Hermes can ensure a strong online presence on different social networking sites, during the social media and e-commerce marketing trend. Hermes sales should be committed to creating a pleasant buying experience for customers, and always strive to perform better and exceed the expectations of customers [12]. Customers who are often satisfied with their shopping experience will make positive statements about the company and recommend its services to friends, partners, or others.…”
Section: Opportunitymentioning
confidence: 99%